The Effectiveness of RMS Learning Model in Improving Metacognitive Skills on Science Basic Concepts - MUHLISIN, Ahmad; SUSILO, Herawati; AMIN, Mohamad; ROHMAN, Fatchur (Journal of Turkish Science Education, 2018)
This study aimed at: 1) Examining the effect of RMS learning model to metacognitive skills. 2)Examining the effect of different academic abilities against metacognitive skills. 3) Examining the effect of interaction between RMS learning model and different academic abilities against metacognitive skills. This study is quasi experiment which employed pretest and posttest non equivalent group design. The instrument of this study was essay test with high level of reliability 0.712. Descriptive analysis and ANACOVA statistical analysis were applied to analyze the obtained data. The results showed that RMS learning model effectively improved metacognitive skills and able to aligned students’ metacognitive skills in different academic abilities. The highest indicator metacognitive skills are shown on the indicator planning with descriptions set goals with a value of 90%. The impact of RMS learning models was 51.5% higher than conventional models on metacognitive skills.